2023
DOI: 10.1172/jci170733
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage–endothelial cell crosstalk orchestrates neutrophil recruitment in inflamed mucosa

Abstract: Neutrophil (PMN) mobilization to sites of insult is critical for host defense and requires transendothelial migration (TEM). TEM involves several well-studied sequential adhesive interactions with vascular endothelial cells (ECs); however, what initiates or terminates this process is not well-understood. Here, we describe what we believe to be a new mechanism where vessel-associated macrophages through localized interactions primed EC responses to form ICAM-1 “hot spots” to support PMN TEM. Using real-time int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Recent studies show that vascular-associated macrophages (VAM) promote highly localized ICAM1 expression in ECs initiating EC-neutrophil adhesive interactions. 27 Perivascular microglia could also physically contact with ECs and modulate the expression of tight junction protein claudin-5. 28 In this study, we showed an improvement of claudin-5 expression after a transient reduction of resident macrophages in bAVMs, which further indicates that the resident macrophages play roles in maintaining BBB integrity and priming inflammation in disease conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that vascular-associated macrophages (VAM) promote highly localized ICAM1 expression in ECs initiating EC-neutrophil adhesive interactions. 27 Perivascular microglia could also physically contact with ECs and modulate the expression of tight junction protein claudin-5. 28 In this study, we showed an improvement of claudin-5 expression after a transient reduction of resident macrophages in bAVMs, which further indicates that the resident macrophages play roles in maintaining BBB integrity and priming inflammation in disease conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil and ECs interaction allows for unidirectional migration through venular walls ( 54 , 60 , 61 ). Most importantly, aberrant neutrophil-endothelial interactions are implicated in a wide range of inflammatory diseases that relate to neutrophil influx and tissue damage ( 62 64 ). Similarly, neutrophil-epithelial crosstalk is involved in the maintenance of the epithelial-lined organs where uncontrolled neutrophil processes contribute to pathogenesis of diseases ( 65 68 ).…”
Section: Neutrophil Biology: the Basicsmentioning
confidence: 99%
“…As such, tumor EC-derived IL-6 induces alternative polarization and immunosuppressive phenotypes in perivascular macrophages [155]. In addition, Lyve-1 + macrophages have a critical role in creating a pro-angiogenic TME through maintaining and expanding a perivascular mesenchymal cell population, ultimately establishing a specialized niche that supports tumor progression [156]. Macrophage-derived TNF-α and endothelial TNF receptor are identified as crucial components of this regulatory mechanism.…”
Section: Perivascular Macrophagesmentioning
confidence: 99%